Ac voltage converter using pwm technique as soft starter for single phase induction motor / Mohamad Zaidi Ismail - Ismail, Mohamad Zaidi (2011)
This thesis report presents pulse width modulation (PWM) method in AC voltage converter as a soft starter of an induction motor. This technique is used to limit the starting currents that occur in an induction motor. The starting current limiting device for single phase induction motor is driven by an AC power supply. This technique is usually used in household electrical equipment to reduce an inrush starting current at initial startup. When the induction motor is turn ON, high starting current will flow in the induction motor. The propose system capable to reduce some portions of positive and negative periods in sinusoidal waveform of the AC power such that the average voltage input to the single phase induction motor is increase gradually due to the increasing of PWM duty cycle. Thus, the initial high starting current of an induction motor can be reduced and the average input voltage to the induction motor could be increased gradually